Work Engagement in the Face of Terrorism: The Moderating Role of Trait Resilience. Issue 4 (20th April 2020) - Malik, Omer Farooq; Shahzad, Asif; Raziq, Muhammad Mustafa
ABSTRACT: Drawing on conservation of resources theory, we examine the relationships between perceived risk of terrorism, fear of terrorism, and work engagement. In addition, we aim to investigate whether trait resilience reflecting a positive personality characteristic moderates the negative effects of terrorism risk perceptions and feelings of fear on work engagement. The sample of the study comprised 361 frontline health workers of polio eradication initiative in three major cities of Pakistan. Data were collected using a self-administered questionnaire and hypotheses were tested using the PROCESS macro. We found that perceived risk of terrorism positively predicts fear of terrorism that, in turn, negatively predicts work engagement. Further, trait resilience attenuated the negative impacts of perceived risk of terrorism and fear of terrorism on work engagement. We contribute to the literature by demonstrating that individuals' ability to remain psychologically engaged in their work can be negatively impacted by terrorism risk perceptions and feelings of fear, but these impacts were weaker at high levels of trait resilience compared to low levels. We also discuss a number of practical implications and suggest future research directions.